Calibrating bacterial evolution - Ochman, Howard (The National Academy of Sciences, 1999)
Attempts to calibrate bacterial evolution have relied on the assumption that rates of molecular sequence divergence in bacteria are similar to those of higher eukaryotes, or to those of the few bacterial taxa for which ancestors can be reliably dated from ecological or geological evidence. Despite similarities in the substitution rates estimated for some lineages, comparisons of the relative rates of evolution at different classes of nucleotide sites indicate no basis for their universal application to all bacteria. However, there is evidence that bacteria have a constant genome-wide mutation rate on an evolutionary time scale but that this rate differs dramatically from the rate estimated by experimental methods.